Konsep Fiqh Ibadah Imam al-Ghazali Dalam Kitab Ihya Ulum al-Din - M. Nur Agus Salim (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2008)
This study aims to examine Imam al-Ghazali's concept of the fiqh of worship as contained in the book Ihya Ulum al-Din, with a focus on the integration of the outward (fiqh) and inward (tasawuf) aspects of worship. This study uses a qualitative method with a literature study approach, analyzing the contents of the book Ihya as well as relevant classical and contemporary references. The results showed that Imam al-Ghazali offered an approach to the fiqh of worship that not only emphasized the formal aspects of the law, but also brought to life the spiritual meaning of each practice. He combined the disciplines of fiqh and Sufism to form a form of worship that was not only valid according to Islamic law, but also solemn and spiritually valuable. This study shows the relevance of al-Ghazali's thinking in building a holistic dimension of worship, which touches on both legal aspects and the purification of the soul.